2022
DOI: 10.1002/ueg2.12289
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide prevalence and burden of gastroparesis‐like symptoms as defined by the United European Gastroenterology (UEG) and European Society for Neurogastroenterology and Motility (ESNM) consensus on gastroparesis

Abstract: Background/Objectives The global epidemiology of gastroparesis is unknown. The European UEG and European Society for Neurogastroenterology and motility consensus defines Gastroparesis as a condition characterized by delayed gastric emptying in the absence of mechanical obstruction, with a symptom pattern of nausea and/or vomiting and overlapping postprandial distress syndrome (PDS). Real‐world evidence of this gastroparesis‐like symptom pattern is a crucial step in understanding the epidemiology of gastropares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
(71 reference statements)
2
21
0
Order By: Relevance
“…In order to establish the epidemiology of GP, the prevalence of subjects with the appropriate symptom pattern needs to be known, as well as the proportion of those in whom delayed GE can be confirmed. A recent study from the Rome IV Global Epidemiology survey showed symptoms suggestive of GP affected 0.9% of the adult population worldwide 25 . In the current study, we used a database of subjects who underwent a GE study and filled out symptom questionnaires, allowing us to evaluate the prevalence of delayed emptying in those with GPLS according to the European consensus, in comparison to patients who underwent GE testing and who did not fulfil these symptom criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In order to establish the epidemiology of GP, the prevalence of subjects with the appropriate symptom pattern needs to be known, as well as the proportion of those in whom delayed GE can be confirmed. A recent study from the Rome IV Global Epidemiology survey showed symptoms suggestive of GP affected 0.9% of the adult population worldwide 25 . In the current study, we used a database of subjects who underwent a GE study and filled out symptom questionnaires, allowing us to evaluate the prevalence of delayed emptying in those with GPLS according to the European consensus, in comparison to patients who underwent GE testing and who did not fulfil these symptom criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several disorders can be associated with gastroparesis, but the predominant types are idiopathic and diabetic. The estimated global prevalence is 0.9%, with a higher prevalence of 1.3% in diabetic subjects 13 …”
Section: Gastric Motor and Sensory Functionmentioning
confidence: 99%
“…The estimated global prevalence is 0.9%, with a higher prevalence of 1.3% in diabetic subjects. 13 While nausea and vomiting are cardinal gastroparesis symptoms, most patients with these symptoms will not show delayed gastric emptying. They are categorized according to the Rome IV consensus as having chronic nausea and vomiting syndrome, cyclic vomiting syndrome or cannabinoid hyperemesis syndrome.…”
Section: Gastric Motility Disordersmentioning
confidence: 99%
“…Anyhow, from the same Rome Foundation Global Epidemiology Study database, a specific symptom pattern was used as the definition of gastroparesis, such as nausea and/or vomiting ≥1 day/week and simultaneous postprandial distress syndrome, and this was reported by 0.9% of adults. 4 The high prevalence of both the gastroduodenal and gastroparesis‐like symptom clusters and the associated effects they have on health outcomes, including increased healthcare consumption, indicate the need for effective treatment options to reduce symptoms. The recent United European Gastroenterology (UEG) and European Society for Neurogastroenterology and Motility consensus on gastroparesis 5 that was based on a Delphi process of agreement on evidence‐based statements disappointingly showed that only the dopamine‐2 antagonists and 5‐HT4 agonists are recommended for usage.…”
mentioning
confidence: 99%